Character Education of Islamic Boarding School Students in the 4.0 Industrial Revolution Era : Literature Review: Pendidikan Karakter Siswa Pondok Pesantren Di Era Revolusi Industry 4.0: Literature Riview - Rohman, Abd; Muhid, Abdul (Halaqa: Islamic Education Journal, 2022)
Character education is one of the important ways that must be done to equip the nation's next generation in undergoing the industrial era 4.0. One of them is character education through Islamic religious learning which has been carried out in Islamic boarding schools. Islamic boarding schools are undoubtedly supported in shaping the character of Santri/Students, that is what motivated the author to write this Literature Review article. In this study, the data acquisition process uses a qualitative method with a literature review approach using a bibliography from journals, articles or books. The main meaning or problem that will be discussed in writing paragraphs in this literature review is the character education of Islamic boarding school students in the industrial 4.0 era